ARAHAN PENATAAN JALUR PEJALAN KAKI DI KAWASAN PUSAT KOTA RUTENG BERDASARKAN KRITERIA KEAMANAN (Jurnal Planesa (Planologi), 2016)
Pasar Ruteng Road is a road corridor in Ruteng City whose land function is dominated by commercial land, allowing people to walk to reach each access. However, pedestrian path conditions that are not yet compatible with user needs and other activities on pedestrian paths, such as street vendors and illegal parking of motor vehicles result in many pedestrians using the road shoulder to walk. Therefore, the main objective of this research is to provide guidance for pedestrian path arrangement in central area of Ruteng City, especially in Pasar Baru Road Market corridor to be safer for every pedestrian path user, especially for children, parents, and people with disabilities. This study uses an IPA analysis to analyze perceptions of satisfaction level and pedestrian interest on pedestrian path conditions. The variables used in this research are security (Unterman, 1984). The results showed that pedestrian path arrangement based on security criteria included spaceship and vehicle space distribution, broken pedestrian path repair, provision of ferry facilities and markers, provision of kereb / guardrail, and provision of markers for special needs.                Keywords: pedestrian path, directions, city center